Safe Hydration Volume to Prevent Contrast-induced Acute Kidney Injury and Worsening Heart Failure in Patients With Heart Failure and Preserved Ejection Fraction After Cardiac Catheterization. Issue 3 (September 2017) - Bei, Wei-jie; Wang, Kun; Li, Hua-long; Lin, Kai-yang; Guo, Xiao-sheng; Chen, Shi-qun; Liu, Yong; Yi, Shi-xin; Luo, De-mou; Chen, Ji-yan; Tan, Ning
Abstract : Abstract: Few studies have investigated the efficacy and safety of hydration to prevent contrast-induced acute kidney injury (CI-AKI) and worsening heart failure (WHF) after cardiac catheterization in heart failure and preserved ejection fraction (HFpEF; HF and EF ≥50%) patients. We recruited 1206 patients with HFpEF undergoing cardiac catheterization with periprocedural hydration volume/weight (HV/W) ratio data and investigated the relationship between hydration volumes and risk of CI-AKI and WHF. Incidence of CI-AKI was not significantly reduced in individuals with higher HV/W [quartile (Q) 1, Q2, Q3, and Q4: 9.7%, 10.2%, 12.7%, and 12.2%, respectively; P = 0.219]. Multivariate analysis indicated that higher HV/W ratios were not associated with decreased CI-AKI risks [Q2 vs. Q1: odds ratio (OR), 0.95; Q3 vs. Q1: OR, 1.07; Q4 vs. Q1: OR, 0.92; all P > 0.05]. According to multivariate analysis, higher HV/W significantly increased the WHF risk (Q4 vs. Q1: adjusted OR, 8.13 and 95% confidence interval, 1.03–64.02; P = 0.047). CI-AKI and WHF were associated with a significantly increased risk of long-term mortality (mean follow-up, 2.33 years). For HFpEF patients, an excessively high hydration volume might not be associated with lower risk of CI-AKI but may increase the risk of postprocedure WHF.